Pengembangan LKPD Terintegrasi Komik Matematika Berbasis PBL untuk Meningkatkan Kemampuan Representasi Matematis Peserta Didik - Rahmayani, Sekar Ayu; Suwito, Abi; Safrida, Lela Nur; Ambarwati, Reza (Jurnal Pendidikan Matematika : Judika Education, 2026)
The purpose of this research is to develop a mathematics comic-integrated Problem Based Learning (PBL) worksheet to enhance eighth-grade students’ mathematical representation ability in solving quadrilateral problems. The type of research used is development research with the aim of producing a particular product that will be tested for validity, practicality and effectiveness, where the development process is described as thoroughly as possible and then evaluated. The development model used is a 4-D model. Student worksheet with a validity value of 4.43, placing it the valid category. In terms practical criteria are declared practical based on the results of student observations, teacher observations and teacher responses which reach good criteria. Student worksheets meet the effective criteria, as shown by (1) based on classical completeness with a score of 83.33%, (2) based on student response questionnaires with an average score of 94.61% and (3) an average N-Gain score of 72.35%, which is a high increase in mathematical representation abilities. The results of the analysis of the experimental class where learning was carried out using studenta worksheet showed that there were 46.67% of students with high representation abilities and 43.33% of students with medium representation abilities and 10% of students with low representation abilities.So, we can conclude that this student worksheet that has been develop classified as valid, practical and effective worksheet.   Keyword: PBL, Development, Mathematical Comic, Quadrilateral